Study on the Requirements for AI Development and Operation Ethics Centered on Children - Nagayuki Saito (International Telecommunications Society (ITS), 2021)
In recent years, the use of artificial intelligence (AI) has become widespread in society, and the need for ethical considerations regarding its development and operation has been discussed. However, despite the fact that those considerations are equally important for both adults and children, discussions on ethical guidelines based on the impact of international AI on children have not progressed. This study examined the requirements for child-centered AI ethics guidelines based on the United Nations' "Children's Rights Convention." As a result, it became clear that it is necessary to develop AI based on the child's developmental stage, secure a usage environment, and educate the government and industry about the peculiar characteristics of children.
Keywords: 330; Children; Artificial Intelligence (AI); Ethics Guidelines; UNCRC; Rights and Protection